MOTIF SISWA DALAM PEMILIHAN KEGIATAN EKSTRAKURIKULER YANG TIDAK SESUAI MINAT DAN BAKAT DI SMA N 1 SOLOK SELATAN - Aldi Fradana (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The study was based on 30% of 94 people which means 34 people from students who choose extracurricular activities are not based on their interests and talents. Whereas the main purpose of extracurricular activities implemented in schools is to develop the interests and talents of students in SMA N 1 Solok Selatan. The purpose of this study is to describe the student's motives in the selection of extracurricular activities that are not in accordance with interests and talents. The theory used is the theory of phenomenology according to Alfred Schutz. This research uses a qualitative research approach with descriptive type. The type of data used is primary data and secondary data. Data collection methods include observation (non-participant), in-depth interviews and document studies. The unit of analysis of the group. Data analysis was done by Miles and Huberman analysis technique, data presented in four stages 1. Data collection 2. Data reduction 3. Presentation of data 4. Conclusion. The results of this study revealed that the students motives in the selection of extracurricular activities that are not in accordance with their interests and talents because in choosing these activities they get 6 encouragement that is 1) Want to learn new things, 2) Affected Friends, 3) Recommendations of teachers, 4) The demands of parents, 5) More prestigious positions, and 6) To Meet Demands from School.